THE IMPACT OF REAL EARNINGS QUALITY ON THE FUTURE MARKET VALUE BY MODERATED BY THE DIVIDEND POLICY - Markonah Markonah; Muljanto Siladjaja; Nicodemus Simu (Management Research Studies Journal, 2020)
The previous researches concluded that, the investor had to pressure on management for improving the earning quality, because it related with predicting the future prospect with high accuracy. Developing out the new proxy for financial reporting quality, this empirical testing modified the real earnings quality. The dividend policy has advantages in reducing out the cost of capital, so that this policy could be used as a moderated variables. This research used the moderated multiple regression by collecting all data on the listed company in industry manufacturing from 2015-2017. In calculating the future market value, this research used the Model H (Two Stages Model of Growth) in predicting the estimated price, which had fullfilled the minimum tracking signals criteria. The statistical testing shown out the real earnings quality have the positive impact on future market value, where the higher earnings quality have made the investors decision in estimating the future prospect precisely. The dividend policy played a critical role in reducing out the pattern of opportunistics behaviour, when is a pressure on management in having proclivity to improve the earnings quality. This empirical testing had pointed out that publication financial earnings had been implication of game theory. To support the game theory in publication financial performance, this research had provided a novelty in estimating investor s action by providing out the schema of investors perception and accounting information. The dividend policy had proclivity to give a push on management in implementing earning management, because managements effort in dissemating the positive signal.